PERBEDAAN RATA-RATA TEKANAN DARAH SISTOLIK DENGAN STATUS GIZI, KONSUMSI LEMAK DAN SERAT SISWA SMA XAVERIUS 1 PALEMBANG - Podojoyo, Podojoyo; Masnawiyah, Masnawiyah (Publikasi Penelitian Terapan dan Kebijakan, 2013)
Blood pressure in in the teenage years can be used to predict the occurrence of hypertension in the future, it is necessary to know the factors related to the increase in blood pressure. This study aims to determine the average difference between body mass index, fat and fiber consumption patterns with a systolic blood pressure. This study is a cross-sectional survey design, the number of samples in this study are 80 people who were taken by using a multistage sampling and analyzed using independent t test and oneway Anova.The results showed that the greatest percentage of normal nutritional status (70%), the pattern of fat consumption (61.3%), lack of fiber consumption (68.8%), the maximum value of the blood pressure of 168 mmHg. Body mass index, fat and fiber consumption patterns can lead to increased blood pressure. After the analysis shows that there is a difference between the average systolic blood pressure with body mass index, fat and fiber consumption patterns (p <0,05).Students should realize the importance of checking blood pressure regularly so that blood pressure can be controlled early and avoid the consumption patterns of high-fat and low in fiber in order to avoid an increase in blood pressure, as well as pay attention to nutritional status.